Evaluation of aerobic and anaerobic capacity in pubertal karate athletes: performance analysis and development strategies - Korkmaz, K.; Aygören, C.; Düzova, H. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This study investigated the effects of gender`s foot arch structure (normal arch vs. pes planus) on aerobic and anaerobic performance in pubertal karate athletes.